Effect of Self-instructional Module on Knowledge Regarding Lithium Carbonate Therapy among the Staff Nurses in Selected Psychiatric Institutions of Mumbai City - Perke, Jyoti; Kadri, Mosin (Innovational: Journal of Nursing and Healthcare, 2024)
Introduction: Mental illness affects one in every eleven individuals in India, or approximately 50 million Indians are afflicted with psychiatric disorders. Approximately one in ten thousand individuals with psychiatric disorders will experience mood disorders at some point in their lives. Arecent NICE guideline from 2014 designates lithium as the initial maintenance treatment for bipolar affective disorder. Materials and Methods: A quasi-experimental, one group pre-test, post-test design has been adopted to assess the effectiveness of selfinstructional module (SIM) on knowledge, among the staff nurses on lithium carbonate therapy in selected psychiatric institutions. The study was conducted on 60 staff nurses who were working in selected psychiatric institution. Data were collected from May 2021 to July 2021. Astructured questionnaire has been utilized to assess the knowledge of staff nurses about general concept, pharmacodynamics, pharmacokinetics, therapeutic doses, laboratory monitoring, adverse effect, contraindication, measure to prevent adverse effect, management of adverse effects, and nursing implications to be taken while the patient on lithium carbonate therapy. Results: The data revealed that there is a significant difference in mean of pre-test score and mean of post-test score knowledge regarding lithium carbonate therapy among staff nurses in selected psychiatric institutions. The study’s key findings indicate that the SIM concerning lithium carbonate therapy effectively improves the knowledge of staff nurses. No statistically significant correlation was found between demographic variables and staff nurses’ knowledge of lithium carbonate therapy. Conclusion: The study concluded that it is necessary to provide study module on lithium carbonate therapy to enhance the knowledge of staff nurses which is essential.